(untitled) (Res Gesta, 2018)
The official history has contributed to subsume the treatment of indigenous issues traditionally associating it with the border, war and malon, blocking the approach of other dynamic and complex processes that were developed in the framework of the relations established between indigenous and state society . This way of analyzing the past conditioned, for a long time, the treatment and insertion of these topics in the school curriculum. In this paper we focus on problematizing these issues by putting them in dialogue with the treatment of the indigenous issue in the curriculum in the pre–university system (UNLP). In this line, themes are proposed to be addressed in the classroom, as well as varied didactic resources that allow to optimize the knowledge of the original peoples, contributing to reinforce their sociohistorical dimension, making visible the deserved protagonism that these social subjects had in the events of national history.